Recovery of Fermented Spinach (Amaranthus sp.) Concentrate Through Ultrafiltration Membrane Process as Source of Folic Acid for Smart Food Formula - Aspiyanto Aspiyanto; Agustine Susilowati; Puspa Dewi Lotulung; Hakiki Melanie; Yati Maryati (Universitas Gadjah Mada, 2017)
Fermentation process on spinach (Amaranthus sp.) by Kombucha culture was done as an effort to recover naturally folic acid as bioactive components to increase smartness. The experimental activity was done by means of UF membrane (100,000 MWCO) fitted in Stirred Ultrafiltration Cell (SUFC) at stirrer rotation speed 200 and 400 rpm, room temperature, pressure 20 and 40 Psi for 30 min. Result of experimental activity showed that based on both selectivity and recovery of folic acid, process optimization of UF was reached at stirrer rotation speed 200 rpm and pressure 40 Psi. In the optimum condition, SUFC technique was able to recover folic acid in retentate 67.75% and in permeate 97.27% (63.19 µg/mL). Identification of monomer in permeate from the optimum process treatment was find out folic acid monomer with molecular weight (MW) 441.39 and relative intensity 93% at mass spectra T2.32 between m/z 257–304 and glutamic acids monomer with MW 148.57 and relative intensity 0.22% at mass spectra T2.82 between m/z 415–470. Other dominant monomer were folic acid fraction.